GNG13 Is a Potential Marker of the State of Health of Alzheimer’s Disease Patients’ Cerebellum - Sanfilippo, Cristina; Musumeci, Giuseppe; Kazakova, Maria; Mazzone, Venera; Castrogiovanni, Paola; Imbesi, Rosa; Di Rosa, Michelino (Journal of molecular neuroscience, 2021)
Brain regions such as the cerebellum (CB) have been neglected for a long time in the study of Alzheimer’s disease (AD) pathogenesis. In reference to a new emerging hypothesis according to which there is an altered cerebellar synaptic processing in AD, we verified the possible role played by new biomarkers in the CB of AD patients compared with not-demented healthy control subjects (NDHS). Using a bioinformatics approach, we have collected several microarray datasets and obtained 626 cerebella sample biopsies belonging to subjects who did not die from causes related to neurological diseases and 199 cerebella belonging to AD. The analysis of logical relations between the transcriptome dataset highlighted guanine nucleotide–binding protein (G protein) gamma 13 (GNG13) as a potential new biomarker for Purkinje cells (PCs). We have correlated GNG13 expression levels with already widely existing bibliography of PC marker genes, such as Purkinje cell protein 2 (PCP2), Purkinje cell protein 4 (PCP4), and cerebellin 3 (CBLN3). We showed that expression levels of GNG13 and PCP2, PCP4, and CBLN3 were significantly correlated with each other in NDHS and in AD and significantly reduced in AD patients compared with NDHS subjects. In addition, we highlighted a negative correlation between the expression levels of PC biomarkers and age. From the outcome of our investigation, it is possible to conclude that the identification of GNG13 as a potentially biomarker in PCs represents also a state of health of CB, in association with the expression of PCP2, PCP4, and CBLN3.